“WHERE IS THE SNAKES’ HILL?” – A COMPARATIVE ACCOUNT OF THE CULTURAL CHANGES IN ZMIJARNIK (Philological Studies, 2019)
This article examines the cultural changes in the development of the so-called Zmijarnik (Snakes’ Hill), located in the village of Orman, near the City of Skopje, Republic of Macedonia. It is based on the ethnographic data collected within different periods, namely in 1937, 1971 and 2014. The ethnographic findings interpret the ways of interacting between the ‘place’ and people, through people’s perceptions, ideas and behaviours related with a given place that were common at one time and their modifications in another time, until today. Additionally, it examines the spatial changes that occurred over time in the respective place, which prompted cultural changes attributed to it. From a place associated with snakes, i.e. their cult, it had been transformed through time and gradually acquired a new form of Christian significance. A comparative account of the successive stages related to this place interprets its status and significance in the people’s perception over time.
Keywords: zmijarnik, place, snake, church